Employees' rights in the Kurdistan Region: a jurisprudential evaluation study: A Jurisprudential Evaluation Study (Raparin Journal of Humanities (RJH), 2024)
This research aims to show and clarify the rights enshrined in the right of the public employee in the Islamic Sharia emanating from the Holy Qur’an and Sunnah and Sharia policy books. All alike, and legitimate rights manifest in moral and psychological rights and financial rights. Financial rights are formed in salaries, bonuses, retirement, and so on. Moral rights revolve around vacation rights in all their forms, better dealings, defending them, stimulating progress and innovation, and so on. The study relied on the inductive, analytical and survey approach accompanying the list of questionnaires that inquired, and directed questions related to the rights of employees.